The metabolic cross‐talk between epithelial cancer cells and stromal fibroblasts in ovarian cancer progression: Autophagy plays a role. Issue 4 (19th September 2017) - Thuwajit, Chanitra; Ferraresi, Alessandra; Titone, Rossella; Thuwajit, Peti; Isidoro, Ciro
Abstract: Cancer and stromal cells, which include (cancer‐associated) fibroblasts, adipocytes, and immune cells, constitute a mixed cellular ecosystem that dynamically influences the behavior of each component, creating conditions that ultimately favor the emergence of malignant clones. Ovarian cancer cells release cytokines that recruit and activate stromal fibroblasts and immune cells, so perpetuating a state of inflammation in the stroma that hampers the immune response and facilitates cancer survival and propagation. Further, the stroma vasculature impacts the metabolism of the cells by providing or limiting the availability of oxygen and nutrients. Autophagy, a lysosomal catabolic process with homeostatic and prosurvival functions, influences the behavior of cancer cells, affecting a variety of processes such as the survival in metabolic harsh conditions, the invasive growth, the development of immune and chemo resistance, the maintenance of stem‐like properties, and dormancy. Further, autophagy is involved in the secretion and the signaling of promigratory cytokines. Cancer‐associated fibroblasts can influence the actual level of autophagy in ovarian cancer cells through the secretion of pro‐inflammatory cytokines and the release of autophagy‐derived metabolites and substrates. Interrupting the metabolic cross‐talk between cancer cells and cancer‐associated fibroblasts could be an effective therapeutic strategy to arrest the progression and prevent the relapse of ovarian cancer.